Vasomotor menopausal symptoms: is it just hot flashes? Alternative non-hormonal methods of treatment with proven effectiveness (literature review) - V. N. Kasyan; L. V. Adamyan (Медицинский совет, 2021)
Taking into account the modern life expectancy, a third of their lives, on average, women live in conditions of estrogen deficiency, which negatively affects the quality of life and the level of morbidity in older people. For doctors of other specialties, besides ObGyn, the climacteric period is strongly associated exclusively with hot flashes. However, early menopausal symptoms include sleep disturbances, mood changes, the risk of depression and decrease in self-esteem, sexual dysfunction. The predominance of vegetative symptoms makes the patient seek help not only from the gynecologist, but also from other specialists, however, the lack of knowledge in menopause medicine leaves them unsatisfied. In this regard, a therapeutic approach requires a comprehensive understanding of the problem.The “gold standard” for managing patients with climacteric complaints is menopausal hormone therapy. However, there are women with contraindications to this group of drugs or the predominance of vegetative symptoms, when only hormonal correction is not enough. Among alternative non-hormonal agents, inhibitors of serotonin reuptake, in particular the most popular drug venlafaxine, hold a strong leadership with proven efficacy against a complex of symptoms. Also, other medications have been studied that can stop both vasomotor and vegetative symptoms of menopause. The review presents the literature data on the role of alternative agents in the correction of vasomotor symptoms of menopause, along with the known efficacy against autonomic complaints for increasing the effectiveness of counseling for older women.